Utilization of Waste Paper as Fiber for Motorcycle Fender Manufacturing Raw Materials - Aljufri, Aljufri; Riskan, Ardi; Rizki, Muhammad Nuzan; Putra, Reza; Akmal, Syarifah (Jurnal Teknologi, 2025)
The selection of paper as the main material for making composites in this study is driven by several considerations. HVS paper is produced by factories with the main raw material being wood. Besides, the use of HVS paper as a fiber for composites offers the potential to reduce industrial waste and reduce dependence on conventional raw materials. The purpose of this study was to determine the effect of variations in the volume fraction of HVS pulp fiber on the mechanical properties of the specimen surface and hardness test to determine the use of HVS pulp composites as raw material for making motorcycle fenders. The benefits of this research provide information for the manufacturing industry in developing innovative composite materials, offering sustainable alternatives that are environmentally friendly, increasing the use value of HVS paper processing, which has only been used as waste. From the results of the research conducted, the results obtained with the value: the hardness of the specimen with a volume fraction variation of 70% fiber has the highest average hardness value of 11.5 kg/mm2, and the variation of the volume fraction of 50% fiber has the lowest average hardness value of 8.6 kg/mm2, which has a difference of 2.9 kg/mm2 with a volume fraction variation of 70% fiber. The highest impact price value is obtained at a 70% pulp volume fraction with an average impact price of 0.0402 J/mm², while the lowest pulp composite impact price is at the volume fraction of 70% fiber. 50% pulp with an impact price of 0.0263 J/mm². The increase in hardness and impact resistance with increasing pulp volume explains that this composite can be an alternative material for application on motorcycle fenders.